2003
DOI: 10.1128/jvi.77.15.8555-8561.2003
|View full text |Cite
|
Sign up to set email alerts
|

Length of Epstein-Barr Virus Termini as a Determinant of Epithelial Cell Clonal Emergence

Abstract: Reiterated terminal sequences of Epstein-Barr virus (EBV) DNA are numerically heterogeneous among infectious virions, providing a viral measure of clonality in infected cells. After in vitro infection, carcinoma cells bearing EBV episomes with fewer terminal repeats (TRs) proliferated faster. In single-cell clones, TR number varied inversely to the quantity of latent membrane protein 2A (LMP2A) transcripts whose unspliced precursors cross joined TRs. Thus, EBV clonality may reflect selection for a TR number th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…Previous studies were unable to discern any growth advantage in EBV LMP2A-expressing Akata cell clones compared to vector control cells (44,49). Previous studies already had indicated an important role for LMP2A in the regulation of the growth of epithelial cells in cultures (35,44). Members of the caspase family of proteases have been shown to be key executioners in the apoptotic process in many cell types in response to diverse apoptotic stimuli (8,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies were unable to discern any growth advantage in EBV LMP2A-expressing Akata cell clones compared to vector control cells (44,49). Previous studies already had indicated an important role for LMP2A in the regulation of the growth of epithelial cells in cultures (35,44). Members of the caspase family of proteases have been shown to be key executioners in the apoptotic process in many cell types in response to diverse apoptotic stimuli (8,14).…”
Section: Discussionmentioning
confidence: 99%
“…LMP2A not only alters cell growth in epithelial cells (35,44) but also inhibits TGF-␤1-induced apoptosis through activation of the PI3-K/Akt pathway in the gastric carcinoma cell line HSC-39. In particular, EBV-associated gastric carcinoma cells express a limited number of EBV genomes, including EBV nuclear antigen 1, EBV-encoded small RNAs, BARF0, and LMP2A (19,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative rates of DNA synthesis in cell clones were quantified by 5-bromo-2Ј-deoxyuridine (BrdU) incorporation assays using the in situ cell proliferation kit Competitive clonal outgrowth assays were performed as previously described (42). Briefly, cellular clones distinguishable by the molecular size of EBV-fused termini were combined in mixed culture, passaged every 48 h, and assessed after each passage for the emergence of a predominant cell clone as determined by changes in relative intensity of TR bands by Southern blotting.…”
Section: Methodsmentioning
confidence: 99%
“…The first source of diversity comes from the circularization of the EBV DNA double-stranded molecule via the terminal repeats during virion production in the saliva. 11 As a second source of diversity, allelic polymorphisms of EBNAs genes define type 1 and type 2 EBV isolates. 12 In addition, LMP1-BNLF1 gene polymorphisms, the most discriminating genetic locus, reflect intrastrain diversity.…”
Section: Introductionmentioning
confidence: 99%